2019
DOI: 10.1177/1758835919874649
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LSINCT5 promotes endometrial carcinoma cell proliferation, cycle, and invasion by promoting the Wnt/β-catenin signaling pathway via HMGA2

Abstract: Background: A review of the evidence has indicated the critical role of long noncoding RNA (lncRNA) LSINCT5 in a large number of human cancers. However, the mechanistic involvement of LSINCT5 in endometrial carcinoma (EC) is still unknown. Here the authors aim to characterize the expression status of LSINCT5 and elucidate its mechanistic relevance to EC. Methods: Relative expression of LSINCT5 and HMGA2 were quantified by a real-time polymerase chain reaction. SiRNAs were employed to specifically knockdown end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…We further explored the potential role of ceRNA network mechanism regulated by RP11-89K21. promoted proliferation, invasion and metastasis of EC cells by regulating HMGA2/Wnt/β-catenin signaling pathway [45]. LncRNA OGFRP1 promoted the malignant progression of endometrial carcinoma by regulating the miR124-3p/SIRT1 axis and activating the PI3K/AKT/GSK-3β pathway [46].…”
Section: Resultsmentioning
confidence: 99%
“…We further explored the potential role of ceRNA network mechanism regulated by RP11-89K21. promoted proliferation, invasion and metastasis of EC cells by regulating HMGA2/Wnt/β-catenin signaling pathway [45]. LncRNA OGFRP1 promoted the malignant progression of endometrial carcinoma by regulating the miR124-3p/SIRT1 axis and activating the PI3K/AKT/GSK-3β pathway [46].…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown that lncRNAs affects the initiation and development of tumors by regulating a variety of molecular mechanisms and signaling pathways. Researchers observed lncRNA LSINCT5 promoted proliferation, invasion and metastasis of EC cells by regulating HMGA2/Wnt/β-catenin signaling pathway [45]. LncRNA OGFRP1 promoted the malignant progression of endometrial carcinoma by regulating the miR124-3p/SIRT1 axis and activating the PI3K/AKT/GSK-3β pathway [46].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study indicated that the expression of MYC target genes was inhibited in response to the downregulation of Gcn5 histone acetyltransferase activity, contributing to apoptosis of lymphoma cells (60). c-MYC was also found to be repressed in response to long stress-induced non-coding transcript 5 knockdown, which inhibited tumor cell proliferation, thereby stimulating apoptosis of cells (61).…”
Section: Discussionmentioning
confidence: 99%